Francisella induced microparticulate caspase-1/gasdermin-D activation is regulated by NLRP3 independent of Pyrin. - Srabani Mitra; Erin Dolvin; Karthikeyan Krishnamurthy; Mark D Wewers; Anasuya Sarkar (PLoS ONE, 2018)
Although the study of pathogen sensing by host defense systems continues to uncover a role for inflammasome components specific to particular pathogens, gaps remain in our knowledge. After internalization, Francisella escapes from the phagosome in mononuclear cells and is thought to be detected by intracellular pathogen-response-receptors pyrin and Aim2 in human and murine models, respectively. However, it remains controversial as to the role of pyrin in detecting Francisella. Our current work aims to study the contribution of inflammasome sensor, Pyrin in regulating microparticulate caspase-1/GSDM-D activation by Francisella. Our findings suggest that NLRP3 is central to the activation/release of active caspase-1/GSDM-D encapsulated in microparticles (MP) by Francisella. We also provide evidence that this regulation is independent of pyrin, implicated in sensing cytosolic Francisella in NLRP3-/- conditions where endogenous Pyrin is present. Absence of NLRP3 completely abrogated Francisella mediated MP caspase-1/GSDM-D activation and release both before and after internalization of the pathogen. However, deletion of pyrin not only enhanced both LPS and Francisella mediated MP active caspase-1/GSDM-D release, but pyrin overexpression resulted in a reduction of inflammasome activation and release; suggesting an inhibitory role of pyrin in LPS and Francisella mediated MP responses. This NLRP3 dependence and inhibitory effect of pyrin correlated with cytokine release as well. These observations also correlated with MPs ability to induce cell death; as LPS and Francisella-induced MPs from pyrin-deficient cells were more potent than wild-type monocytes whereas, NLRP3-/- MPs failed to induce cell death. Taken together, we report that NLPR3 not only mediates Francisella induced cytokine responses, but is also critical for cytokine-independent microparticle-induced inflammasome activation and endothelial cell injury independent of pyrin.